Konsep Strategi Word of Mouth Marketing dalam Peningkatan Pengembangan Bisnis : Suatu Tinjauan Literatur - Edi Irawan (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This article aims to review and seek to inform about the concept of word of mouth marketing strategy in enhancing business development. The research method used is qualitative and literature studies or library research. Based on the results and discussion, it can be concluded theoretically that to understand the concept of word of mouth marketing strategy in improving business development requires several important things, namely: (a) Word of mouth marketing dimensions consisting of talkers, topics, tools, talking part and tracking, (b) Creating word of mouth for a product through: The product must be able to evoke an emotional response and the product must have something that can advertise itself or inspire someone to ask about it.